Effect of the second generation and third generation biofuel blend on performance, emission and combustion characteristics of CI engine. Issue 7 (6th June 2020) - Boopathi, D.; Thiyagarajan, S.; Edwin Geo, V.; Madhankumar, S.
ABSTRACT: The present work aims to utilise second-generation biofuel, namely jatropha oil (JO) and third-generation biofuel, namely waste tire pyrolysis oil (TPO) to replace diesel in a CI engine completely. However, fuel from a single source cannot fulfil the energy requirement. Hence, multiple sources of alternative fuels are necessary. JO has high viscosity, while TPO has low cetane number and high sulfur content. The merits and demerits of JO and TPO are mutually balanced, and the optimum blend matching the diesel performance will be identified. The engine used for this study is a single-cylinder CI engine producing 4.4 kW power at a constant speed of 1500 rpm. JO and TPO are blended in various proportions on a volume basis of 75% JO and 25% TPO (JO75 + TPO25), JO50 + TPO50 and JO25 + TPO75 and tested at different load conditions. Compared with diesel, JO exhibits poor combustion due to high viscosity leading to higher soot. Blending TPO with JO improves the performance and reduces soot considerably due to lower viscosity of TPO. With about 5% improvement in BTE and significant NO-soot tradeoff, JO50 + TPO50 is identified optimum to replace diesel in CI engine.